Seasonal Effects In Selected Six Asian Stock Markets : Are They Still Relevant? - Nik A Majid, Nik Aqilah (2014)
The study investigates the existence of seasonal anomaly by testing four calendar anomalies; day-of-the-week (DOW) effect, week-of-the-month (WOM) effect, week-of-the-year (WOY) effect and month-of-the-year (MOY) effect. According to the seasonal anomalies concept, the stock index market prices are against the Efficient Market Hypothesis (EMH) theory due to the inconsistency of the index prices. The validity of seasonal anomalies is examined based on a sample of selected six Asian stock markets. The results show that (1)DOW effect can be seen in selected stock markets, (2) only Week 2 signifies the existence of WOM effect, (3) Week 44, Week 45 and Week 48 significant results justify the presence of WOY effect, and (4) January effect on the study of MOY effect are absent from the selected stock markets. Association to this study, it further justify the existence of seasonal anomaly in today’s financial market, especially in the selected six Asian countries. This will help investors to make suitable investment strategies in order to respond to the market inefficiency.